Color Degradation of Napthol Jeans with TiO2-SiO2 Photocatalyst from Karangwuni Beach Sand, Kulon Progo - Shinta Amelia; Lukhi Mulia Shitopyta; Mila Utami W; Ida Sriyana (Eksergi, 2023)
The industries that produce the most liquid waste in Indonesia are the batik and textile industries. Napthol dyes are the most widely used dyes as dyes or batik dyes which are completely non-biodegradable and can cause cancer, digestive disorders, and weakening of the body's resistance due to disease and environmental pollution. One of the processing methods currently being developed to degrade color in liquid waste is the photocatalyst method. The photocatalyst method can use a photocatalyst semiconductor in the form of TiO2 with a supporting material in the form of SiO2. SiO2 as a supporting material can be obtained from the utilization of the local potential of Karangwuni Kulon Progo beach sand. Dye processing was carried out by varying the irradiation time and concentration of Naphtol Jeans. The degradation process was applied to a 25 ml sample solution with the addition of 5 gr/L catalyst for 24 hours, 48 hours, 72 hours, 96 hours, and 120 hours of irradiation. This study resulted in the highest reduction in naphtol concentration at the concentration variable of 100 ppm with a percentage of 44.4687% and a long irradiation time of 120 hours.